To study the factors that contribute the awareness of Amanah Saham Gemilang (ASG) products towards investors in Kuala Lumpur / Azeril Syafik Roslan and Farah Amirah Mohd Jais - Roslan, Azeril Syafik; Mohd Jais, Farah Amirah (Faculty of Business and Management, 2014)
This research is conduct to carry out the “To study the factors that contribute the awareness of Amanah Saham Gemilang (ASG) products towards investors in Kuala Lumpur”. In order to investigate the differ findings from other previous researcher, we have decided the relationship between knowledge, marketing strategies and social influence are factors that contribute the awareness of Amanah Saham Gemilang (ASG) products towards investors in Kuala Lumpur. The objectives of this research are to investigate the relationship between knowledge, marketing strategies and social influence that are the factors that contribute the awareness of Amanah Saham Gemilang (ASG) products towards investors in Kuala Lumpur as well as to determine the most significant influencing factor that contribute the awareness of Amanah Saham Gemilang (ASG). Besides questionnaire as primary data, all the data were obtained from the secondary data. Journals and related information were obtained from Internet and journals. The variables will be analyzed by using the frequency distribution, the reliability analysis, descriptive statistical analysis, correlation analysis and multiple regression analysis. As results, we found that knowledge, marketing strategies and social influence have significant relationship with awareness of Amanah Saham Gemilang (ASG) whereas marketing strategies is most factors that contribute the awareness of Amanah Saham Gemilang (ASG) products towards investors in Kuala Lumpur.